Bacterial Growth Enhancement Value and Nutritional Quality of Compounded Milk Media from Commercial Milk Brands - Olopade, Bunmi; Oyawoye, Olubukola Monisola; Oranusi, Solomon Uche; Obafemi, Yemisi Dorcas; Onibokun, Elizabeth Adeola (Applied Food Biotechnology, 2020)
Background and Objective: Milk agar is recommended for enumeration of microorganisms in dairy products. Most of the commonly used media are imported to Nigeria and hence available in-house substitutes are necessary. In this study, microbial growth enhancement values of compounded milk agar were compared to imported milk agar using two milk brands. Dawadawa (fermented locust beans), yeast powder and peptone in the proportions of 1: 3: 5, respectively, were used as nutrient sources. Material and Methods: Growth enhancement values of the compounded media were assessed on three bacterial species of Staphylococcus aureus, Escherichia coli and Lactobacillus plantarum. Furthermore, imported milk agar served as the control. Results and Conclusion: Significant differences were seen in nutritional contents of the compounded milk agar and imported milk agar as well as the elemental compositions of compounded milk agar and imported milk agar. No significant differences were seen between the total viable counts of Staphylococcus aureus and Lactobacillus plantarum on compounded milk agar and imported milk agar. However, significant differences were reported in the total viable counts of Escherichia coli on compounded milk agar and imported milk agar. Media containing Cowbell milk powder recorded the highest total viable counts (1.3 ´ 105, 1.8 ´ 106 and 2.0 ´ 106 CFU ml-1) for Staphylococcus aureus, Escherichia coli and Lactobacillus plantarum, respectively. In conclusion, the Cowbell milk powder in combination with yeast extract and peptone is the best milk of choice for compounding milk agar when using local resources. Conflict of interest: The authors declare no conflict of interest.